RESTRUKTURISASI BADAN KETAHANAN PANGAN DAN PELAKSANA PENYULUHAN DALAM MEWUJUDKAN KETAHANAN PANGAN DI KOTA BANDARLAMPUNG - Rahayu Sulistiowati; Dara Virginia (Wacana Publik, 2018)
Government has a role in maintaining resilience by organizing arrangements, fostering, controlling and controlling food availability. The Bandar Lampung City Government restructured the Department of Agriculture, Plantation and Livestock. Restructuring was carried out to maximize the government's duty to maintain food security, also because the conditions of food security in the city of Bandar Lampung were very worrying. This article aims to evaluate the implementation of the Food Security Agency's restructuring and describe the factors that support and hinder the implementation of the restructuring of the Food Security Agency and Implementing Counseling for the Extension of Food Security in Bandar Lampung City. This article uses the Good Governance paradigm based on the new management approach proposed by Hughes in Sulistio. This article uses a qualitative descriptive type with data analysis using the method proposed by Miles and Hubberman with the stages of data reduction, data presentation and ending with the withdrawal of the group. This article concludes that there is a restructuring within the Food Security Agency and Executing Agency for Food Security in Bandarlampung City, there are five organizational elements that influence the implementation of restructuring.